Expanding Sentience: Tibetan Buddhismand the Possibility of Plant, Bacteria, and AI Sentience - Simonds, Colin H. (Canadian Journal of Buddhist Studies, 2023)
This article explores the possibility and implications of expanding the Tibetan Buddhist definition of sentient being to phenomena outside of the traditional Buddhist realms of rebirth. It first establishes the traditional Buddhist view of sentience to serve as a basis for comparison before exploring some of the ways that contemporary scientists and philosophers have extended sentience to plants, microorganisms, and technology like LaMDA. These two traditions are then brought into conversation with one another to evaluate these claims of sentience from a Buddhist position, and precedents in the Tibetan tradition are identified for ascribing sentience to plants, bacteria, and so forth. Finally, the implications of this broader understanding of sentience on the cosmological, soteriological, and ethical strands of Tibetan Buddhism will be considered to offer some ways for contemporary Buddhists to engage an increasingly posthuman world.,